Penerapan Manipulating Fabric Cording Dan Spiral Boning Pada Busana Pesta Dengan Sumber Ide Bunga Anggrek - Safira Juwita Permatasari; Wahyuningsih, Urip (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
This research aims to describe the final results of applying manipulating fabric cording and spiral boning to evening wear, inspired by orchid flowers, which creates a unique impression rich in meaning with the fibers of the orchid. The main materials used are duchess fabric and jacquard fabric, applying manipulating fabric cording and spiral boning, starting with determining the application on evening wear. The cording stage uses sewing techniques and hidden stitches, while for spiral boning various tools are used, including strings, wires, and balline. The created garment uses an L silhouette, showcasing a body-hugging mermaid shape at the torso that flares at the bottom. This design is enhanced with tail details located on both sleeves, creating a look that conveys a unique impression, reinforcing the character of the garment that gives a sexy and unique feel. This research uses the double diamond model research method which has four stages: discover, define, develop, and deliver. The result of this research is to understand the application of manipulating fabric cording and spiral boning in party wear with the source of inspiration being orchids.